Theoretical investigation of the effects of N-substitution on the photophysical properties of two series of iridium(iii) complexes. (29th January 2015) - Shang, Xiaohong; Han, Deming; Zhan, Qing; Zhou, Defeng; Zhang, Gang
Abstract : The effects of N-substitution on the photophysical properties of two series of iridium(iii ) complexes have been theoretically investigated, which can tune the emission color and enhance the photoluminescence quantum efficiency. Abstract : Based on the complexes [Ir(dfb-pz)2 (tfmtyp)] (1 ) and [Ir(tfmfb-pz)2 (tfmtyp)] (2 ) [dfb-pz = 2, 4-difluorobenzyl- N -pyrazole; tfmtyp = 2-(5-trifluoromethyl-[1, 2, 4]triazol-3-yl)-pyridine; tfmfb-pz = 2-tri-fluoromethyl-5-fluorobenzyl- N -pyrazole], two series of Ir(iii ) complexes have been designed by substituting "CH" groups with the N atom at -a, -b, -c, and -d positions on the pyridine moiety in N^N ligands. The electronic structure, absorption and emission spectra as well as phosphorescence efficiency of all these Ir(iii ) complexes were investigated by using density functional theory (DFT) and time-dependent DFT (TDDFT) methods. The calculated results show that the assumed complexes1a and2a may possess a higher photoluminescent quantum efficiency than other complexes and are potential candidates as efficient blue-emitting materials. This study shows that the N substitution can tune the emission color of1 and2 and enhance the photoluminescence quantum efficiency.